PERAN EKONOMI KREATIF DALAM MENINGKATKAN PARIWISATA DI SAMPURAGA KECAMATAN PANYABUNGAN BARAT KABUPATEN MANDAILING NATAL - Nurintan Siregar (Program Studi Ekonomi Syariah Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2024)
Mandailing Natal Regency is the southernmost district of North Sumatra, covering 6,620.7 km2 (9.23%) of the island. With 23 Districts and 386 settlements, the population is around 413,750 people. The legend of Sampuraga is one of the folktales from Mandailing Natal District, North Sumatra Province. This legend is related to the Sampuraga Pond tourist attraction which is located in Sirambas Village, West Panyabungan District. This Sampuraga folklore legend tells of a disobedient child who was cursed by his mother. This study uses a descriptive qualitative analysis method. The researcher's goal in this analytical, descriptive is to describe current events through methodical analysis and presentation of facts to make it easier to understand and draw conclusions. This study uses primary and secondary data as sources. The main information for this study was collected through interviews conducted according to pre-planned interview standards. In addition, it is supported by secondary data from connected organizations, including from organizations in the form of studies, literature, publications, reports, and others. materials related to this research.